Lack of efflux mechanism in a clinical isolate of Pseudomonas aeruginosa highly resistant to beta-lactams and imipenem - Kadry, A A (Folia microbiologica, 2003)
An isolate of Pseudomonas aeruginosa from cystic fibrosis was highly resistant to beta-lactams and beta-lactamase inhibitors. The resistant determinants of clinical isolate to imipenem, ceftazidim, cefriaxone and cefepime were conjugally nontransferable. The slow or nonenzymically mediated breakdown of imipenem and other broad-spectrum beta-lactams suggested the resistance of P. aeruginosa isolate to these drugs which may be attributed to both permeability and efflux. Impaired penetration of imipenem and other beta-lactams through the membrane was detected by a diminished expression of outer-membrane proteins of approximate molar mass of 46 and 39 kDa, matched to OprD and OprF, respectively. Efflux resistance mechanism for meropenem and beta-lactams has been ruled out since the isolate failed to express outer-membrane protein of approximately 50 kDa which is matched to the OprM protein channel. Thus, reduced permeability in the clinical isolate is the main mechanism conferring resistance against beta-lactams including imipenem.
Keywords: Drug Resistance, Multiple, Bacterial; aktivní transport; Imipenem; Bacterial Outer Membrane Proteins; mnohočetná bakteriální léková rezistence; antibakteriální látky; ceftazidim; membránové transportní proteiny; Cystic Fibrosis; Microbial Sensitivity Tests; Ceftriaxone; poriny; elektroforéza v polyakrylamidovém gelu; Cell Membrane Permeability; Biological Transport, Active; Membrane Transport Proteins; permeabilita buněčné membrány; imipenem; Electrophoresis, Polyacrylamide Gel; konjugace genetická; lidé; Pseudomonas aeruginosa; cystická fibróza; Cephalosporins; Anti-Bacterial Agents; Genes, Bacterial; ceftriaxon; Humans; Porins; mikrobiální testy citlivosti; cefepim; Ceftazidime; Cefepime; Conjugation, Genetic; cefalosporiny; proteiny vnější bakteriální membrány; bakteriální geny